Early bone formation around immediately placed two-piece tissue-level zirconia implants with a modified surface: an experimental study in the miniature pig mandible - Roland Glauser; Peter Schupbach (SpringerOpen, 2022)
Abstract Purpose To histologically examine early bone formation around transmucosal implants and to evaluate the influence of surface characteristics on early peri-implant bone healing using a miniature pig model. For this, commercially available dental implants with a rough zirconia (YTZP) surface were compared to surface-modified Ti control implants at 4 and 8 weeks after placement. Methods Immediately following the extraction of six mandibular premolars, 20 two-piece, tissue-level, screw-shaped YTZP implants (Patent™ Standard Zirconia Implant ø4.1 × 11 mm) with a modified rough blasted before sintering surface were inserted in four adult miniature pigs. In addition, four titanium (Ti) tissue-level implants (Straumann® Standard RN ø4.1 × 10 mm Roxolid®) with a moderate surface (SLActive®), one per animal, were placed as control implants. A histological analysis was performed on the hard tissues after 4 and 8 weeks of transmucosal healing. Results The results show a high rate of osseointegration of the test YTZP dental implants at 4 and 8 weeks following insertion. At 4 weeks, a bone-to-implant contact ratio (BIC) of 73.7% (SD ± 16.8) for the test implants (n = 10) and 58.5% for the first control implant was achieved. The second control implant had to be excluded from analysis. At 8 weeks, a BIC of 82.4% (SD ± 16.9) for the test implants (n = 9) and 93.6% (SD ± 9.1) (n = 2) for the control implant was achieved. No statistical difference was observed comparing 4 and 8 weeks YTZP data (p = 0.126). Conclusions The results indicate a predictable osseointegration of immediate zirconia implants with a modified YTZP implant surface and a high degree of BIC present at 4 weeks following insertion. After 8 weeks of healing both the zirconia implants and the Ti implants show a BIC indicating full osseointegration. Further studies involving a larger sample size with more time points are needed to confirm these results.